Digital Realization of PIλDμ Controllers: Performance Evaluation on MCUs and FPGAs - Akgul, Berke; Ersoy, Hakan; Akpinar, Emin; Kartci, Aslihan; Ayten, Umut Engin (IEEE, 2024)
Fractional-Order Proportional-Integral-Derivative controller, also known as (PID mu)-D-lambda, controllers have attracted great interest in recent years due to their superior performance of many control operations. In this work, we provide a study on (PID mu)-D-lambda controllers, with a particular focus on their implementation in a digital environment using microcontroller units (MCUs) and field programmable gate arrays (FPGAs). The study covers mathematical modeling, discretization approaches, and practical implementation. Various performance measures, including resource utilization, power consumption, and throughput, are evaluated for distinct microcontroller unit (MCU) and field-programmable gate array (FPGA) architectures. The results illustrate the compromises between power consumption and computational throughput, offering valuable information on choosing the most suitable hardware platforms for (PID mu)-D-lambda controller applications.
Keywords: Digital Signal Processing; FPGA; Fractional-order calculus; IIR Filter; PID; (PID mu)-D-lambda; Engineering